Intercalation of Copper Phthalocyanine Within Bulk Graphite as a New Strategy Toward the Synthesis of CuO-Based CO Oxidation Catalysts - Couvret, Gaëlle; Genay, Ghislain; Robert, Cerise; Michel, Loïc; Caps, Valérie (Frontiers in Chemistry, 2020)
Graphite is a widely available natural form of carbon with peculiar chemical and surface properties. It is essentially hydrophobic and consists in very stable stacks of graphene layers held together by highly delocalized pi-pi interactions. Its use in chemistry and in particular for catalytic applications requires modification of its structure to increase its surface area. This is commonly achieved by harsh oxidation methods which also modifies the chemical composition of graphite and enables subsequent deposition of catalytic phases via common impregnation / reduction methods. Here we show that copper phthalocyanine (CuPc) can be incorporated into unmodified bulk graphite by the straight-forward sonication of a dimethylformamide solution containing CuPc and graphite flakes. Immobilization of the CuPc complex in the graphitic matrix is shown to rely on pi-pi interactions between the Pc ligand and graphenic surfaces. This strong CuPc-graphene interaction facilitates oxidation of the graphitic matrix upon oxidation of the immobilized complex, as shown by thermogravimetric analysis in air. Nevertheless, a soft oxidation treatment can be designed to produce CuO nanoparticles (NPs) without degrading the dispersing graphitic matrix. These well-dispersed CuO NPs are shown (1) to decrease the degree of stacking of graphite in the solid-state by intercalation in-between graphitic stacks, (2) to be more easily reducible than bulk CuO and (3) to be catalytically active for the oxidation of carbon monoxide. The higher mass-specific CO oxidation rates observed, as compared with CuO/alumina benchmarks, highlight the beneficial role of the carbon support and the relevance of this new strategy towards the design of copper oxide catalysts from copper phthalocyanine metal complexes.